A Study of Quality Assessment of Practice Guidelines for the Emergency Drill in Caring for Patients with High-Risk Infectious Diseases, Emerging Diseases, and Re-emerging Diseases at Bamrasnaradura Infectious Disease Institute Using the AGREE II Framework - Sumalai, Piyawadee; Ardsorn, Chanchai; Matsree, Kasama (Journal of Bamrasnaradura Infectious Diseases Institute, 2026)
Emergency drills for High-Risk Infectious Diseases, Emerging, and Re-emerging Diseases are crucial for hospital preparedness. However, assessing the quality of practice guidelines used in these drills using international standards remains understudied. This study aimed to evaluate the quality of practice guidelines for the care of patients with dangerous infectious, emerging, and re-emerging diseases at the Bamrasnaradura Infectious Diseases Institute, and to develop efficient guidelines tailored to the Institute's specific context. This descriptive research was conducted among a purposive sample of 90 healthcare personnel at the Bamrasnaradura Infectious Diseases Institute who completed all stages of the 2025 drills. The research instruments included a general information questionnaire and the AGREE II instrument (covering 6 domains and 20 items). Data were analyzed using percentage, mean, standard deviation, and Pearson’s correlation coefficient. The findings revealed that the overall quality of the guidelines was at a high level, with a mean score of 12.89 out of a total of 15 (Mean = 12.89). The domain with the highest score was "Scope and Purpose", whereas "Editorial Independence" received the lowest mean score. Correlation analysis indicated that the quality assessment based on the AGREE II instrument demonstrated very high internal consistency, which was statistically significant at the .01 level. Furthermore, duration of employment was significantly and positively correlated with patient care experience. This study implies that drills or simulation plans for the care of patients with dangerous infectious, emerging, and re-emerging diseases should prioritize 'Editorial Independence,' given that this domain obtained the lowest average score. Relevant agencies or guideline developers should explicitly enhance the transparency of the working committee and ensure that external parties exert no influence over the content of the guidelines. Additionally, since the duration of employment was positively correlated with patient care experience, consideration should be given to selecting personnel with extensive tenure and high experience to serve as the core team for guideline development. Alternatively, a mentorship system should be established to facilitate knowledge transfer from highly experienced professionals to the newer generation of staff.